Determination of binding characteristics as a measure for effective albumin using different methods - Paar, Margret; Fengler, Vera H.; Reibnegger, Gilbert; Schnurr, Kerstin; Waterstradt, Katja; Schwaminger, Sebastian P.; Stauber, Rudolf E.; Oettl, Karl (Biochimica et biophysica acta. General subjects, 2023)
Transport functions of albumin are of clinical and pharmacological interest and are determined by albumin's properties like posttranslational modifications or bound ligands. Both are affected in pathological conditions and in therapeutic grade albumin solutions. The term effective albumin concentration was introduced as a measure of functionally intact albumin. Our aim was to evaluate the impact of ligands and modifications with different approaches as a measure of effective albumin. We used a spin labelled fatty acid and dansylsarcosine to characterize binding properties of albumin i) prepared from plasma of patients and healthy control donors, ii) measured directly out of plasma, iii) research grade albumin, iv) in vitro modified albumin, and v) therapeutic infusion solutions before and after removal of stabilizers. Bilirubin is the main determinant for binding function in patients' albumin. In in vitro prepared albumin bound fatty acids correlated with impaired binding. Human nonmercaptalbumin1, not human nonmercaptalbumin2, showed reduced binding properties. Binding and transport function of therapeutic albumin was severely impaired and restored by filtration. Glycation of research grade albumin had no effect on the binding of dansylsarcosine and only a minor effect on fatty acid binding. Our results suggest that effective albumin -in terms of binding properties- is primarily determined by bound ligands and only to a minor extent by posttranslational modifications. Characterizing albumin directly from plasma better reflects the physiological situation whereas in the case of therapeutic grade albumin stabilizers should be removed to make its binding properties accessible. •Primarily bound ligands and to some extent redox state determine albumin binding properties.•Liver patients' and pharmacological albumin show similar characteristics.•Removal of ligands/stabilizers improves binding ex vivo and in infusion solutions.